2014
DOI: 10.1007/s10530-014-0751-9
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the predatory impacts of the “demon shrimp” Dikerogammarus haemobaphes, on native and previously introduced species

Abstract: Biological invasions continue to exert pressure on ecosystems worldwide and we thus require methods that can help understand and predict the impacts of invasive species, on both native species and previously established invaders. Comparing laboratory derived functional responses among invasive and native predators has emerged as one such method, providing a robust proxy for field impacts. We used this method to examine the likely impacts of the Ponto-Caspian amphipod Dikerogammarus haemobaphes, known as the ''… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 68 publications
0
30
1
Order By: Relevance
“…Although D. haemobaphes is known to be a predator (Kinzler et al 2009;Bovy et al 2015), our experiment showed a small but non-significant predation impact upon G. pulex. The minimal IGP impact on G. pulex is in direct contrast to its congener D. villosus whose predation impacts on G. pulex are well documented (MacNeil and Platvoet 2005;Kinzler et al 2009;MacNeil et al 2011).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Although D. haemobaphes is known to be a predator (Kinzler et al 2009;Bovy et al 2015), our experiment showed a small but non-significant predation impact upon G. pulex. The minimal IGP impact on G. pulex is in direct contrast to its congener D. villosus whose predation impacts on G. pulex are well documented (MacNeil and Platvoet 2005;Kinzler et al 2009;MacNeil et al 2011).…”
Section: Discussioncontrasting
confidence: 52%
“…This could be a result of D. haemobaphes' predaceous behaviour and preference for high energy food, e.g. animal prey and tissue (Kinzler et al 2009; Bacela-Spychalska and van der Velde 2013; Bovy et al 2015). It is known that more nutritious animal diets lead to accelerated growth and maturity in amphipods (Delong et al 1993;Berezina et al 2005;Gergs and Rothhaupt 2008) which allows rapid population expansion, an advantageous trait of invading species.…”
Section: Discussionmentioning
confidence: 99%
“…The most widely distributed of these is Dikerogammarus haemobaphes (demon shrimp), which was first recorded in the UK in 2012 (Bovy et al 2015). A second invasive amphipod, Dikerogammarus villosus (killer shrimp), was first recorded in the UK 2010 (MacNeil et al 2010) and to date is geographically confined to five known locations (GBNNSS 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The invasive amphipods of D. villosus and D. haemobaphes, have been reported to display greater predatory tendencies than native or established nonnative amphipod species in the UK (Bacela-Spychalska and Van der Velde 2013;Dodd et al 2014;Bovy et al 2015) and have been observed to inflict 'bite' injuries on prey (Dick et al 2002). In addition, detrital processing efficiency of invasive amphipods has been reported to be lower than that of native amphipod species resulting in a potential modification of energy flows within invaded ecosystems (MacNeil et al 2011;Piscart et al 2011;Constable and Birkby 2016;Jourdan et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…in ballast water tanks) and become established in new locations-where resources might be in short supply or already being utilised by existing native species. Similarly, invader establishment and spread may be facilitated by resource use patterns, again measurable by functional response studies, and species invasiveness as distinct from ecological impact (see Ricciardi and Cohen 2007) may also be correlated with functional responses (see Bovy et al 2015;Xu et al 2016). One aspect that might considerably improve the use of functional responses in such contexts would be incorporation of abundance, as per Parker et al (1999), which is essentially the numerical response that, together with the functional response, gives the total response (or total uptake rate; see Dick et al 2014).…”
mentioning
confidence: 99%